Special Monitoring of Bonded Zone Companies as a Source of State Revenue at Bogor Customs and Excise Office - Nurdiansyah, Amril; Kristian Suhartadi Widi Nugraha (International Journal of Business and Quality Research, 2025)
Special monitoring is a mechanism carried out to identify potential non-compliance and ensure that customs obligations are fulfilled by companies receiving bonded zone facilities. The study was conducted using a descriptive-narrative approach by utilizing and processing data on invoices from special monitoring results in 2024 and 2025 at Bogor Type A Customs and Excice Supervision and Service Office. This study examined the extent of the contribution of state revenue from special monitoring to the 2025 state revenue target. The results showed that special monitoring made a real contribution to state revenue, with a total realization of 11.47 billion rupiah by November 1, 2025. This contribution is still relatively small, namely 1.65% of the total state revenue target in 2025 (693.79 billion rupiah); therefore, the role of special monitoring is still complementary. However, when viewed from the aspect of contribution to the increase in revenue targets from 2024, which amounted to 70.07 billion rupiah, invoices from special monitoring have a significant impact of 16.38%.